Addition of radium-223 to abiraterone acetate and prednisone or prednisolone in patients with castration-resistant prostate cancer and bone metastases (ERA 223): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 3 (March 2019) - Smith, Matthew; Parker, Chris; Saad, Fred; Miller, Kurt; Tombal, Bertrand; Ng, Quan Sing; Boegemann, Martin; Matveev, Vsevolod; Piulats, Josep Maria; Zucca, Luis Eduardo; Karyakin, Oleg; Kimura, Go; et al.
Summary: Background: Abiraterone acetate plus prednisone or prednisolone improves progression-free survival and overall survival in patients with metastatic castration-resistant prostate cancer. Radium-223 improves overall survival and delays the onset of symptomatic skeletal events in patients with castration-resistant prostate cancer and bone metastases. We assessed concurrent treatment with abiraterone acetate plus prednisone or prednisolone and radium-223 in such patients. Methods: We did a randomised, double-blind, placebo-controlled, phase 3 trial at 165 oncology and urology centres in 19 countries. Eligible patients were aged 18 years or older, and had histologically confirmed, progressive, chemotherapy-naive, asymptomatic or mildly symptomatic castration-resistant prostate cancer and bone metastases, Eastern Cooperative Oncology Group performance status of 0 or 1, life expectancy of at least 6 months, and adequate haematological, renal, and liver function. Participants were randomly assigned (1:1) according to a permuted block design (block size 4) via interactive response technology to receive up to six intravenous injections of radium-223 (55 kBq/kg) or matching placebo once every 4 weeks. All patients were also scheduled to receive oral abiraterone acetate 1000 mg once daily plus oral prednisone or prednisolone 5 mg twice daily during and after radium-223 or placebo treatment. The primary endpoint was symptomatic skeletal event-free survival, which was assessed in the intention-to-treat population. Safety analyses were done in all patients who received at least one dose of any study drug. This trial is registered with ClinicalTrials.gov, number NCT02043678 . Enrolment has been completed, and follow-up is ongoing. Findings: Between March 30, 2014, and Aug 12, 2016, 806 patients were randomly assigned to receive radium-223 (n=401) or placebo (n=405) in addition to abiraterone acetate plus prednisone or prednisolone. The study was unblinded prematurely, on Nov 17, 2017, after more fractures and deaths were noted in the radium-223 group than in the placebo group (in an unplanned ad-hoc analysis), but all patients had completed radium-223 or placebo before this date. At the primary analysis (data cutoff Feb 15, 2018), 196 (49%) of 401 patients in radium-223 group had had at least one symptomatic skeletal event or died, compared with 190 (47%) of 405 patients in the placebo group (median follow-up 21·2 months [IQR 17·0–25·8]). Median symptomatic skeletal event-free survival was 22·3 months (95% CI 20·4–24·8) in the radium-223 group and 26·0 months (21·8–28·3) in the placebo group (hazard ratio 1·122 [95% CI 0·917–1·374]; p=0·2636). Fractures (any grade) occurred in 112 (29%) of 392 patients in the radium-223 group and 45 (11%) of 394 patients in the placebo group. The most common grade 3–4 treatment-emergent adverse events were hypertension (43 [11%] patients in the radium-223 group vs 52 [13%] patients in the placebo group), fractures (36 [9%] vs 12 [3%]) and increased alanine aminotransferase concentrations (34 [9%] vs 28 [7%]). Serious treatment-emergent adverse events occurred in 160 (41%) patients in the radium-223 group and 155 (39%) in the placebo group. Treatment-related deaths occurred in two (1%) patients in the radium-223 group (acute myocardial infarction and interstitial lung disease) and one (<1%) in the placebo group (arrhythmia). Interpretation: The addition of radium-223 to abiraterone acetate plus prednisone or prednisolone did not improve symptomatic skeletal event-free survival in patients with castration-resistant prostate cancer and bone metastases, and was associated with an increased frequency of bone fractures compared with placebo. Thus, we do not recommend use of this combination. Funding: Bayer.